Hsp90 Interacts With Tm-22 and Is Essential for Tm-22-Mediated Resistance to Tobacco mosaic virus - Qian, Lichao; Zhao, Jinping; Du, Yumei; Zhao, Xijuan; Han, Meng; Liu, Yule (Frontiers in Plant Science, 2018)
The tomato gene Tm-2(2) encodes a coiled coil-nucleotide binding site-leucine rich repeat type resistance protein, which confers effective immune response against tobamoviruses by detecting the presence of viral movement proteins (MPs). Here we report that the N.benthamiana Heat shock protein 90 (Hsp90) specifically interacts with Tm-2(2). Silencing of Hsp90 compromised Tm-2(2)-mediated resistance against Tobacco mosaic virus (TMV) and reduced the steady-state levels of Tm-2(2) protein. In addition, we found that Hsp90 associates with SGT1 in yeast and in plant cells. These results suggest that Hsp90-SGT1 complex takes part in Tm-2(2)-mediated TMV resistance by functioning as chaperone to regulate Tm-2(2) stability.